Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1046/j.1365-2435.2002.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability estimates do not always set an upper limit to heritability

Abstract: Summary1. The concept of repeatability, the measurement of consistent individual differences, has become an increasingly important tool in evolutionary and ecological physiology. Significant repeatability facilitates the study of selection acting on natural populations and the concept has several practical implications for identifying traits. 2. When properly defined and measured, repeatability can set the upper limit to heritability. This is potentially a very useful interpretation of the repeatability of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(77 citation statements)
references
References 43 publications
0
72
1
Order By: Relevance
“…First, we estimated the repeatability estimate of the probability to copy. The repeatability estimate for a trait provides a maximal value for its heritability (Lynch and Walsh, 1998; but see Dohm, 2002), therefore informing about the possible heritability estimate. However, because of high mortality and breeding dispersal rates in our population, individuals very rarely mate with the same partner over several years (less than 2% in our sample), and thus we could not estimate the repeatability of the probability to copy at the pair level, but estimated it first only at the individual level.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…First, we estimated the repeatability estimate of the probability to copy. The repeatability estimate for a trait provides a maximal value for its heritability (Lynch and Walsh, 1998; but see Dohm, 2002), therefore informing about the possible heritability estimate. However, because of high mortality and breeding dispersal rates in our population, individuals very rarely mate with the same partner over several years (less than 2% in our sample), and thus we could not estimate the repeatability of the probability to copy at the pair level, but estimated it first only at the individual level.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Furthermore, our ability to detect a functional relationship between these performance traits depends on high repeatability of individual performance [17]. The repeatability of a trait also determines the upper limit on heritability and represents an estimate of its potential to react to directional selection [[27], but see [28]]. Without repeatability in performance, selection is unlikely to distinguish between high and low performance levels and there would be no directional selection on locomotor performance.…”
Section: Discussionmentioning
confidence: 99%
“…2 can be greater than t under special circumstances [23], a review of available estimates did not suggest these circumstances were met and suggested that these instances were instead a product of estimation error. This screening reduced the dataset to 71 estimates.…”
Section: Materials and Methods (A) Datasetmentioning
confidence: 99%